Prevalence and antibiotic susceptibility pattern of pathogens from urinary tract infections (UTI) in a private diagnostic laboratory in Bangladesh (Asian Journal of Medical and Biological Research, 2020)
Urinary tract infection (UTI) is one of the commonest infections encountered by clinicians and despite the widespread availability of antimicrobial agents UTI has become difficult to treat because of appearance pathogens with increasing resistance to antimicrobial agents. The aim and objectives of this study were to determine the pathogens causing UTI and to determine the antibiotic sensitivity status among these isolates in a diagnostic laboratory in Dhaka city. A laboratory based cross sectional survey was conducted in Popular Diagnostic Centre Ltd. Dhanmondi, Dhaka-1205, Bangladesh from July 2016 to December 2016. A total of 553 freshly voided midstream urine samples (10-20 ml) were collected in a wide mouth sterile container from patients and processed in microbiology laboratory to isolate pathogens and antibiotic susceptibility test using standard procedure. Among 553 urine sample, the culture positivity in urine samples was found to be 158 (28.57%) of which 39 (24.70%) were isolated from male patients and 119 (75.30%) from female patients. Escherichia coli (43.67%) were found to be the predominant pathogen followed by Staphylococcus spp. (16.45%), Enterococcus spp. (13.39%), Klebsiella spp. (13.29%), Candida spp. (5.70%), Acinetobacter spp. (4.43%), Psudomonas spp. (3.80%) and Proteus spp. (1.27%). Carbapenem group (Imipenem, Meropenem) were the most effective antibiotic with resistance between 0 and 5.1% of the gram negative isolates and Linezolid and Vancomycin was most effective in gram positive isolates. Nitrofurantoin was most effective both gram negative and gram positive isolates. This study finding showed That Escherichia. coli isolates were the predominant pathogens and showed increasing pattern to the commonly prescribed drugs in private practice that in turn leaves the clinicians with very few alternative options in drug for the treatment of UTIs.Asian J. Med. Biol. Res. September 2020, 6(3): 564-569